Consumo y hábitos alimentarios en el ámbito escolar y valoración antropométrica del estado nutricional de los niños y niñas del grado quinto de la institución Educativa Gabriel plazas del municipio de Villlavieja (2022)
Introduction: For the year 1975 the obesity rate in childhood and adolescence was 1%, increasing by 2016 by 6-8%. In Latin America and the Caribbean, 30% of children between 5 and 19 years of age are overweight and obese. This could be explained by the preparation or purchase of unhealthy lunch boxes. Methodology: Cross-sectional descriptive observational study, carried out in 38 children in the fifth grade of a public educational institution. Consumption and eating habits were evaluated through the application of a 27-question questionnaire; Likewise, nutritional status, through anthropometric classification and use of nutritional classification tables. Results: 50% of children present alterations in nutritional status, being excess weight the most frequent. Regarding food in the school environment, more than half of the children reported eating non-nutritious products such as bread with additives, sugary drinks and fried foods. Average daily consumption of fruits, vegetables, and dairy products is higher in children of normal weight compared to children who are overweight. Conclusions: Boys and girls have bad eating habits associated with the consumption of packaged products, with a high content of sugar and saturated fat in their lunch boxes. Additionally, a significant percentage of boys and girls are obese or overweight.Introduction: For the year 1975 the obesity rate in childhood and adolescence was 1%, increasing by 2016 by 6-8%. In Latin America and the Caribbean, 30% of children between 5 and 19 years of age are overweight and obese. This could be explained by the preparation or purchase of unhealthy lunch boxes. Methodology: Cross-sectional descriptive observational study, carried out in 38 children in the fifth grade of a public educational institution. Consumption and eating habits were evaluated through the application of a 27-question questionnaire; Likewise, nutritional status, through anthropometric classification and use of nutritional classification tables. Results: 50% of children present alterations in nutritional status, being excess weight the most frequent. Regarding food in the school environment, more than half of the children reported eating non-nutritious products such as bread with additives, sugary drinks and fried foods. Average daily consumption of fruits, vegetables, and dairy products is higher in children of normal weight compared to children who are overweight. Conclusions: Boys and girls have bad eating habits associated with the consumption of packaged products, with a high content of sugar and saturated fat in their lunch boxes. Additionally, a significant percentage of boys and girls are obese or overweight.